Exfoliation-induced O-doped g-C3N4 nanosheets with improved photoreactivity towards RhB degradation and H2 evolution. Issue 7 (23rd February 2022) - Yan, Juntao; Liu, Jinhong; Sun, Ya; Ding, Deng; Wang, Chunlei; Sun, Linbing; Li, Xiaofang
Abstract : Graphitic carbon nitride (g-C3 N4 ) nanosheets exfoliated from their bulk-sized counterparts are limited by a quantum size effect-induced widened bandgap. Abstract : Graphitic carbon nitride (g-C3 N4 ) nanosheets exfoliated from their bulk-sized counterparts are limited by a quantum size effect-induced widened bandgap. In this work, an (NH4 )2 S2 O8 (APS) induced thermal exfoliation approach is introduced to fabricate O-doped g-C3 N4 nanosheets (OCNs). During this calcination process, the thermal decomposition products (NH3 and H2 SO4 ) from APS not only efficiently promote delamination, but also introduce O doping into the g-C3 N4 structure, realizing the synchronization control of the electronic structure and morphology. Compared to the bulk g-C3 N4, OCNs show exceptional enhancement of the photocatalytic degradation of RhB and H2 evolution, owing to their enlarged specific surface area, more active edges exposed, and efficient photogenerated carrier separation. This work provides a useful pathway to design and prepare potentially advanced g-C3 N4 .